Inspecting the factors of individualizing and binding moral value orientation in the Moral Foundations Questionnaire-2 for validation—a re-analysis of data from pre-service teachers in Ghana - Wild, Steffen; Fobi, Daniel; Möhring, Michélle (Frontiers in Psychology, 2025)
IntroductionMoral foundation theory postulates two higher-order moral value orientations: individualizing and binding. In the measurement instrument of the Moral Foundations Questionnaire-2 (MFQ-2), 36 items cover the dimensions of authority, care, equality, loyalty, proportionality, and purity, which contribute to people’s individualizing and binding moral value orientation. So far, less research exists for the validation of the moral value structure in so-called non-WEIRD (western, educated, industrialized, rich, and democratic) countries like Ghana. Thus, the question arises: what is the empirical structure of moral value orientations in Ghana, and is it possible to identify the factors of individualizing and binding moral value orientations in line with the theoretical framework?.MethodsWe re-analyse data from 1,049 pre-service teachers at a university in Ghana that were gathered using a cross-sectional design and convenience sampling.ResultsOur re-analyses provide first hints of construct validity as well as criterion validity with the criteria of gender and religiosity. The abovementioned six underlying dimensions could be seen as first-order factors. The assumption of individualizing and binding moral value orientations as second-order factors in the MFQ-2 is weakly supported.DiscussionFindings are reflected upon and discussed in terms of limitations. Further investigations in other populations of non-WEIRD countries are deemed necessary to evaluate the instrument for robustness.